Estimates of global chemotherapy demands and corresponding physician workforce requirements for 2018 and 2040: a population-based study. Issue 6 (June 2019) - Wilson, Brooke E; Jacob, Susannah; Yap, Mei Ling; Ferlay, Jacques; Bray, Freddie; Barton, Michael B
Summary: Background: The incidence of cancer (excluding non-melanomatous skin cancers) is projected to rise from 17·0 million to 26·0 million between 2018 and 2040. A large proportion of these patients would be likely to derive benefit from chemotherapy, but no studies so far have quantified current and projected global chemotherapy demands. We aimed to estimate changes in national, regional, and global demands for first-course chemotherapy and the cancer physician workforce between 2018 and 2040 if all patients were treated according to best-practice evidence-based guidelines. Methods: Data for the incidence of 29 types of cancer in 183 countries in 2018, and projections of incidence in 2040, were obtained from GLOBOCAN 2018. Optimal chemotherapy utilisation from evidence-based guidelines was applied to these incidence data to generate the number of new patients requiring first-course chemotherapy in 2018 and 2040. We then estimated the corresponding cancer physician workforce required to deliver this chemotherapy (on the basis of physicians seeing 150 new patients requiring chemotherapy per year). We did sensitivity analyses to investigate how cancer stage at presentation affected chemotherapy demands. We also did sensitivity analyses to explore changes to workforce requirements if each physician was seeing 100 new patients requiring chemotherapy per year or 300 new patients requiring chemotherapy per year. Findings: Between 2018 and 2040, the number of patients requiring first-course chemotherapy annually will increase from 9·8 million to 15·0 million, a relative increase of 53%. The estimated proportion of patients needing chemotherapy who reside in low-income or middle-income countries was 63% (6 162 240 of 9 782 783) in 2018, and will be 67% (10 071 049 of 14 984 560) in 2040. The most common indications for chemotherapy worldwide in 2040 will be lung cancer (accounting for 2 455 137 [16·4%] of 14 984 560 cases eligible for chemotherapy), breast cancer (1 898 740 [12·7%]), and colorectal cancer (1 678 153 [11·1%]). We estimated that, in 2018, 65 000 cancer physicians were required worldwide to deliver optimal chemotherapy—a figure that we estimate will rise to 100 000 by 2040 (with estimates ranging from from 50 000 to 150 000, depending on workload). Interpretation: Strategic investments in chemotherapy service provision and cancer physicians are needed to meet the projected increased demand for chemotherapy in 2040. Funding: None.